2014
DOI: 10.1371/journal.pone.0108520
|View full text |Cite
|
Sign up to set email alerts
|

Further Characterization of HDAC and SIRT Gene Expression Patterns in Pancreatic Cancer and Their Relation to Disease Outcome

Abstract: Ductal adenocarcinoma of the pancreas is ranking 4 for patient' death from malignant disease in Western countries, with no satisfactory treatment. We re-examined more precisely the histone deacetylases (HDAC) and Sirtuin (SIRT) gene expression patterns in pancreatic cancer with more pancreatic tumors and normal tissues. We also examinedthe possible relationship between HDAC gene expression levels and long term disease outcome. Moreover, we have evaluated by using an in vitro model system of human pancreatic tu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 34 publications
(26 citation statements)
references
References 32 publications
0
24
0
Order By: Relevance
“…We also show the clinical characteristics of all 6 patients in Table 1. It has been reported that invasiveness, inflammation and other disease outcomes are related to HDAC levels and activity 39, 64-66. Invasiveness is one of the vital characteristics of osteosarcoma and it was reported to be related to matrix metalloproteinases-2 (MMP-2) and matrix metalloproteinases-9 (MMP-9)67, 68.…”
Section: Discussionmentioning
confidence: 99%
“…We also show the clinical characteristics of all 6 patients in Table 1. It has been reported that invasiveness, inflammation and other disease outcomes are related to HDAC levels and activity 39, 64-66. Invasiveness is one of the vital characteristics of osteosarcoma and it was reported to be related to matrix metalloproteinases-2 (MMP-2) and matrix metalloproteinases-9 (MMP-9)67, 68.…”
Section: Discussionmentioning
confidence: 99%
“…However, differentiating the exact role of HDAC in acinar proliferation during pancreatitis is precluded by the interference of the inflammatory reaction, thus we cannot exclude the possibility that MS-275 directly inhibits, to some extent, cell cycle progression in acinar cells. Increased HDAC activity is found in human pancreatic cancer cells (McCleary-Wheeler et al, 2013;Ouaissi et al, 2014), and it is essential for cell proliferation, NF-κB activation and EMT transition (Lehmann et al, 2009;Aghdassi et al, 2012). However, since the role of HDAC in pancreatic cancer cells cannot be directly translated to non-transformed acinar cells, additional non-tumour-based experimental models are required to address the role of HDAC in acinar cell proliferation.…”
Section: Ms-275 and Acinar Cell Proliferationmentioning
confidence: 99%
“…Like other cancers, the development of pancreatic cancer is a multistep process with accumulation of genetic and epigenetic changes. Recent studies have revealed many pancreatic cancer-associated deregulated genes and signaling pathways (Chang et al, 2014;Ouaïssi et al, 2014), but the molecular mechanisms underlying the carcinogenesis, progression, and aggressiveness of the cancer have not been fully elucidated.…”
Section: Introductionmentioning
confidence: 99%